Reformulating The Meaning of Pancasila for Recent Indonesia and Its Implication for Constructing Multicultural Education - Suparjo, Suparjo (International Conference of Moslem Society, 2018)
There is a dynamic role and meaning of Pancasila in preserving unity of Indonesia from its early formulation until recent time. This paper aplies a sosio-historical perspective to elaborate the formulation process of Pancasila by Indonesian founding fathers and how the next generation tried to reformulate its values and implement its roles. As well, it applies a pedagogic perspective to reconstruct the implication of such sociohistorical evidences in promoting multicultural education for Indonesian people. Historically, Pancasila was a gentle agreement among national Indonesia leaders who were plural in culture, religion, ethnics and other social backgrounds. However, the dynamic role of Pancasila as both the staats fundamental norms and way of life was matters since the independence of Indonesia 1945 until recent era. As if the coming New Order (Orde Baru: 1971-1997) successfully promoted and preserved Pancasila as the state principle with its elan vital for national stability. New Orde with BP7 (an authoritative councile in formulating the meaning and implementation of Pancasila) and other element forces kept Pancsila; therefore, other formulation meaning of Pancasila were not allowed. The supremy of Pancasila, then, less decreased since the reformation era (1999) and, even, nowdays is quite questionable because of driving global movements. There is no longer strick border line and limitation for people in keeping communication, connection and linkage in the global village. Therefore, Indonesia needs a new way to constitute Pancasila as structural and cultural system of life, namely inclusive life with great commitment to be Indonesia. In this sense, multicultural education becomes a significant pillar to realize it.